Interaction between bacterial adhesins leads to coaggregation by the oral bacteria Veillonella parvula and Streptococcus gordonii - Jack C. Leo (mBio)
ABSTRACT Veillonella parvula is an unusual diderm firmicute that plays a central role in the formation of dental biofilm formation through coaggregation with many other oral bacteria. However, the molecular interactions leading to oral biofilm formation are largely unknown. In a recent study (L. Dorison, N. Béchon, C. Martin-Gallausiaux, S. Chamorro-Rodriguez, et al., mBio 15:e02171-24, 2024, https://doi.org/10.1128/mbio.02171-24), coaggregation by V. parvula was shown to be mediated by trimeric autotransporter adhesins (TAAs), which are large, fibrous surface proteins widespread in Gram-negative bacteria. Importantly, this study identified the binding partner protein on a coaggregating bacterium, Streptococcus gordonii, which the authors called VisA. This finding is the first time a TAA mediating coaggregation with a different type of protein has been established and suggests that specifically interacting protein partners may have coevolved multiple times to allow complex biofilm formation, as exemplified by the development of dental plaque. Understanding these interactions might lead to innovations to reduce build-up of dental plaque and associated oral diseases.